Peran Kepala Sekolah dalam Implementasi Pengembangan Kurikulum 2013 di MTs.S Madrisatul Ikbar Medan Tembung Percut Sei Tuan - Neliwati, Neliwati; Rambe, Jeni Anwar; Dalimunthe, Nadya Salsabilah; Hasibuan, Rani Wardani; Hasanah, Uswatun (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The curriculum reform became part of the improvement of the education system in Indonesia. The study describes the principal's role in implementation of the 2013 curriculum (K-13) ini di MTS.Madrisatul iqbar medan tembung percuma sei tuan. The framing of curriculum and the theory of professionalism to investigate the impact of principal professionalism in the implementation process. Research is of a descriptive qualitative type with phenomenologicalanalysis. Data was collected from the results of interviews against principals, teachers and some randomly selected pupils. The results of the study showed that implementation of K-13 provides autonomy to teachers in curriculum development. The 2013 curriculum demanded an active role thus becoming a stimulus in improving teacher professionalism. K-13 has the potential to form a professional and competitive teacher character. Whereas the principal's role among others became a teacher's participation mediator in curriculum training; the principal became a supervisor; the principal became a participator in regular meetings. The factor that the principal faces consists of a lack of means of K-13-based learning support infrastructure; a lack of student participation in the learning process at the school. The expected implication, for theoretical constructs of research results to be the subject of decision- making considerations in terms of increased quality of education through the curriculum k-13.